Metastatic endophthalmitis caused by Clostridium perfringens. - Nangia, V. (1992)
A case of metastatic endophthalmitis due to Clostridium perfringens originating from the biliary tract is reported. The grave visual prognosis and the importance of early detection and treatment of the primary source of infection are emphasised.